WAYS TO INCREASE INVESTMENTS AND INCOME LEVELS DUE TO CASH FLOWS - Eshonqulov Akmal Qudratovich; Egamkulov Davlatbek Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about ways to increase investment and income levels using cash flows. The article presents the main types of investments, income levels, cash flows, their essence and the economic importance of the flow of funds. The article will consider various types of cash flows, such as private funds flows, securities, foreign currency funds and cryptocurrencies.